Design and analysis of low profile stepped feedline with dual circular patch MIMO antenna and stub loaded partial ground plane for wireless applications - Abdullah Al-Gburi, Ahmed Jamal; Kumar, Praveen; Kumar, Ranjeet; Pal, Pravesh; Sinha, Rashmi; Singh, Ajit Kumar; Mahto, Santosh Kumar; Choubey, Arvind (Electromagnetics Academy, 2024)
A wideband, dual-element MIMO antenna operating in 2.83–7.21 GHz frequency bands is presented in this study. The proposed design consists of a stub-loaded partial ground plane and a stepped feedline with a dual circle-shaped radiator on top. The designed MIMO antenna operates from 2.83 to 7.21 GHz, covering the C band (4–8 GHz) and 5G (sub-6 GHz) applications. The peak gain observed is 4.8 dBi at 6.2 GHz, with a maximum efficiency of 92% at 3.2 GHz. The minimum port isolation and ECC over the bands 2.83–7.21 are observed as 22 dB and 0.003, respectively. To achieve the best outcome, a parametric analysis of the proposed antenna is also simulated. Various diversity characteristic metrics, including diversity gain (DG), mean effective gain (MEG), total active reflection coefficient (TARC), channel capacity loss (CCL), and ergodic channel capacity (CC), are thoroughly analyzed to determine how well the MIMO antenna performs in terms of diversity. In all operating bands, the measured values provide good agreement with simulation results, indicating a strong candidacy for operation in the investigated bands.